Pengaruh Penyuluhan Metode Small Group Discuss terhadap Pengingkatan Pengetahauan tentang TB - Budi Rianto; Nephi Susanti Effendi (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2020)
Tuberculosis is an infectious disease caused by the bacterium mycobacterium. The incidence of tuberculosis in developing countries like Indonesia tends to increase from year to year. Based on data at the Health Office in 2017 there were 78,689 cases of tuberculosis in West Java. Counseling is one of the efforts to increase knowledge. To get good results of knowledge, an appropriate counseling method is needed. The purpose of this study was to determine the effect of counseling on small group discussion (SGD) methods on knowledge about tuberculosis in adult patients at RSUD Sayang Cianjur. This research method uses quasi experiment. Questionnaires were given to respondents before and after counseling. The population in this study were 30 people, with a total sample of 15 respondents in each group. Data collection is done by giving questionnaires to respondents in the form of multiple choise. given before and after counseling. The data in this study were analyzed descriptively to illustrate knowledge before and after counseling. Then it will be analyzed analytically by testing the hypothesis with the Mann-Withneyy test. The results of the analysis obtained p value (0.012) less than α (0.05), it was concluded that there is an influence of the counseling of the SGD method to increase knowledge about TB in adult patients in DOTS Hospital Cianjur. From this research it is recommended to use SGD extension methods to increase knowledge about TB because this method is quite effective in increasing knowledge.